Photo-bio-degradability of agro waste and ethylene-propylene copolymers composites under abiotic and biotic environments - Kumar, A. Pratheep; Pandey, Jitendra K.; Kumar, Bijendra; Singh, R. P. (Journal of Polymers and the Environment, 2006)
Composites were prepared by two methods, (i) graft copolymerization (GFC) of isotactic polypropylene (PP) with maliec anhydride, (MAH) followed by esterification with coir fiber and (ii) by direct reactive mixing (DFC) of polypropylene (PP) and ethylene-propylene (EP) copolymers with MAH and peroxide with coir fiber. These composites, after molding in films (5 x 5 cm, - 100 mu m thickness) were examined for susceptibility to biological attack by measuring the percentage weight loss in compost upto 6 months, periodically, and fungal colonization on surface of the samples, when kept as sole carbon source for the growth of Aspergillus niger in culture medium upto 40 days. Photodegradation was evaluated by monitoring the variations in FT-IR spectrum and crack formation after successive treatment with UV light (>= 290 nm) for 0, 20, 50 and 100 h at 60 C in the presence of air. Specimens of virgin PP were taken as a reference during all period of photo and biodegradation studies. Significant changes were observed depending on the preparation methods during photodegradation and biodisintegration of composites. DFCs samples were disintegrated faster than GFCs during the composting whereas, in culture, GFCs were covered highly in well uniform way by fungi. It was observed that photo-oxidative ageing directly enhanced the biodegradability of composites as the increase in fungal growth rate and decrease in weight during composting were found. It was concluded that extent of compatibilization had a profound effect on photo-oxidation and biodisintegration of composite material; consequently ester bonds were main units during fungal consumption. Composition of monomers in copolymers was also showing significant effect on the degradability which decreased with increasing content of ethylene in ethylene-propylene (EP) copolymers.
Keywords: Biodegradation; biodisintegration and composting; composites; ethylene-propylene copolymers; photo-degradation

Preparation and performance evaluation of EPDM nanocomposites under accelerated weathering - Rana, Sravendra; Tevtia, Amit K.; Kumar, Bijendra; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2006)
The degradability of ethylene propylene diene monomer (EPDM) nanocomposites, prepared from organically modified montmorillonite (CMMT), is studied under accelerated UV irradiation (lambda >= 290 nm) for different time intervals. The development of functional groups during degradation is monitored by FT-IR spectroscopy whereas, surface changes are studied by scanning electron microscopy (SEM). The effect of clay modifier and clay concentration on the degradability are studied. The degradation of neat polymer and composites taking place traditionally and an increase in carbonyl and hydroxyl groups are observed with irradiation time. Neat EPDM is found to be less degradable than nanocomposites. Degradation products, as seen by FT-IR in nanocomposites are found to be the same as in neat polymer but are generated at a faster rate. According to the experimental results, one can define that both ammonium ion and neat montmorillonite (MMT) accelerate the photo-oxidation of EPDM.
Keywords: carbonyl index; Degradation; EPDM; layered silicates; Nanocomposites; photooxidation

Synthesis and characterization of hindered amine light stabilizers based on end functionalization of polypropylene - Reddy, K. Raghunatha; Kumar, Bijendra; Rana, Sravendra; Tevtia, Amit K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
A polymeric hindered amine light stabilizer (HALS), where HALS moiety was attached at the terminal end of the polypropylene chain via end-functionalized vinylidine PP through simple organic reactions, was synthesized. It comprises the synthesis of vinylidine-terminated polypropylene by using Cp2ZrCl2/MAO as catalyst system and epoxidation of vinylidene polypropylene. The final product was synthesized by carrying out the reaction between epoxy end functionalized polypropylene and 4-amino-2,2,6,6-tetrametyl piperidine. The final product was characterized by using H-1 NMR, C-13 NMR, and FT-IR spectra. Functionality was calculated by using vapor phase osmometry and H-1 NMR. The solubility and diffusion coefficient of the product were calculated and also its stabilization performance was checked. (c) 2007 Wiley Periodicals, Inc.
Keywords: end functionalization; functionalization of polymers; polymeric HALS; polypropylene; vinylidine and photostabilization